Recent advances in 3D printing of porous ceramics: A review. Issue 6 (December 2017) - Hwa, Lim Chin; Rajoo, Srithar; Noor, Alias Mohd; Ahmad, Norhayati; Uday, M.B.
Highlights: The compatibility of 3D printing technology for porous ceramics was presented. Various printing techniques used to fabricate porous ceramic were described. The different ceramic powders through 3D printing quality were evaluated and tested. The particle size, flowability and wettability of ceramic powders were evaluated. Different printing parameters and final outcome of porous ceramic were assessed. Abstract: 3D printing, alongside the rapidly advancing field of porous ceramics, is quickly expanding the horizon of what is going to be possible in the future. In this paper, 3D printing technology is evaluated for its compatibility with porous ceramic materials, due to its competitive process in terms of speed and specific tooling, especially for good quality fabrication. The paper reviews the capabilities of these new technology techniques for the fabrication of porous ceramic. The basic technology is the 3D printing techniques, which are used to fabricate porous green ceramic parts that are later sintered. Different ceramic materials are evaluated and the classification of different powders according to their 3D printing quality as well as material aspects is examined. The evaluation of 3D printing process in terms of the powders' physical properties such as particle size, flowability and wettability is also discussed. The relationship between the different 3D printing parameters and the final printing outcome are assessed.